Methods of test for sodium tripolyphosphate (pentasodium triphosphate) and sodium pyrophosphate (tetrasodium pyrophosphate) for industrial use. Determination of loss on ignition Part 4, (28th February 1969) - British Standards Institution,
No abstract available